Penentuan Tarif Jalan Tol Berdasarkan Analisis ATP-WTP, Analisis Sensitivitas dan Persepsi Pengguna Jalan Tol (Hasil Survei Wawancara Jalan Tol Becakayu) - Wiryawan Purboyo; Doddy Ari Suryanto; Tatang Ramdan; Johanes Tendy (Universitas Trisakti, 2023)
The income from toll tariff is the main source of revenue to repayment of investment costs of toll road construction. The estimated value of toll tariffs can be usefull for regulators, investors and BUJT to consider decision KPBU, investment and company management. The aim of this study is to conduct a financial analysis of the toll rates for the Becakayu Toll Road. The research method used is the Quantitative Method, by calculating ATP, WTP, perceptions of applicable tariffs and analyzing the sensitivity of user movement to the toll road. The results of the analysis show that the ATP value is Rp 1,655.00 per km and the WTP value is Rp 1,515.00 per km. The results of the sensitivity analysis of price changes and their probability of moving to the toll road, for each increase in the toll fare (farthest distance) of Rp 3,000.00 has the potential to decrease 0.59% of toll road users. The perception of toll road users regarding the current toll tariff is Rp. 14,000.00 - for a distance of 8.4 km shows that: 51.33% of respondents consider it appropriate; 42.89% consider it expensive; 4.02% is very expensive; 1.61% consider it cheap; and 0.16% consider it very cheap